(3cJGH GdSeWjf aj efGbH GdQShd hGdHJhd hGdeQJVi hGdSHWjfs - (3TeS GdOjf EHQGgje Hf eMeO Hf GdeDjO Hf GHi HcQ Hf eMeO Hf MehjI GdLhjfis
(3ChdgG (B:s
(3JHGQc GdPi fRd GdaQbGf Ydi YHOg djchf ddYGdejf fPjQG hHYO aGdMeO ddg deG GgOjJ Edi MH GdfHi hGgd GdHjJ s
(3BNQgG (B:s
(3hGab NJe gPG GdcJGH HMeO Gddg Gdedc GdhgGH ai PcQ GdaQM GdefJXQ ai LejY GdGfhGA hGaVdfG HTaGYJge eONd UOb Gfc MejO eLjO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW GMjGfkG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs